Heart rate variability in juvenile systemic lupus erythematosus patients - Özge Başaran; İbrahim İlker Çetin; Fatma Aydın; Nermin Uncu; Nilgün Çakar; Filiz Ekici; Banu Çelikel Acar (The Turkish Journal of Pediatrics)
Although neurological involvement has been well recognized in patients with systemic lupus erythematosus (SLE), autonomic nervous system (ANS) involvement has rarely been studied, and has shown conflicting results. The aim of this study was to evaluate the ANS functions by using heart rate variability (HRV) in juvenile patients with SLE. Sixteen juvenile-onset SLE patients and 16 healthy controls were enrolled in the study. All participants underwent 24-hour Holter electrocardiogram monitoring and HRV indices were assessed. The SLE disease activity index (SLEDAI) score was used to assess the disease activity. We analyzed the correlation between disease duration, the SLEDAI score, and the HRV domains. Overall HRV was diminished in patients with SLE compared to controls. There were negative correlations between day and night RMSSD (root-mean-square of the successive normal sinus NN interval differences) and PNN50 (percentage of successive normal sinus NN intervals > 50 ms) values, and SLEDAI (r= -0.588 p=0.017; r= - 0.607 p= 0.013; r= -0.498 p=0.049; r= -0.597 p=0.015, respectively). There were positive correlations between both day and night LF/HF values and SLEDAI (r=0.766 p=0.001; r=0.635 p=0.008, respectively). The results suggest that autonomic dysfunction exists in juvenile patients with SLE. As these children are at increased risk for cardiovascular disease, they need to be assessed for the development of autonomic dysfunction.